Validity and reliability of the Neonatal Discharge Assessment Tool - Girgin, Burcu Aykanat; Cimete, Gueler (Wiley, 2016)
Purpose. To investigate the reliability and validity of the Neonatal Discharge Assessment Tool (N-DAT) designed to assess risk factors related to infants' and parents' readiness for discharge to home. Design and Methods. The sample was composed of 238 high-risk preterm infants, born at gestational age of 24 to 37 weeks, and their parents. High scores on the N-DAT indicated higher risk for discharge of preterm infants and their parents. Psychometric analyses of the N-DAT included content validity, internal consistency reliability, and construct validity. Results. Content validity of the N-DAT items was supported by experts (content validity index = .98). Internal consistency reliability was supported by a Cronbach's alpha for the total instrument of .94. N-DAT total and subscale score correlations ranged from .42 to .89. Known-groups analysis indicated that infants born at < 31 weeks' gestation and infants who were rehospitalized during 8 weeks after discharge had significantly higher N-DAT total and subscale scores than infants born at >= 31 weeks or not rehospitalized. Also, mothers who reported experiencing problems with infant care at home had significantly higher N-DAT Competencies subscale scores than mothers who did not report problems. Practice Implications. The N-DAT is a reliable and valid instrument to evaluate the risks related to discharge of preterm infants so that nurses can provide parents with the necessary knowledge, skills, and resources they need prior to discharge.
Keywords: Neonatal discharge assessment; preterm infant; tool; validity and reliability